2013
DOI: 10.1177/1538574413478474
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endostapling Systems for Vascular Endografts (T)EVAR—Systematic Review—Current State

Abstract: The results are not conclusive. With endostaple systems, patients with difficult anatomic features and high risk can potentially be treated. These systems might reduce the high reintervention rates after endovascular aneurysm repair. Controlled randomized trials with larger number of patients are warranted with endostapling use in primary endograft implantation and for use in reintervention for late endoleaks or endograft migrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Furthermore, implantation is contraindicated when one must overcome >2-mm gaps in undersized endografts or gaps due to dilation of the neck after EVAR. 1,4,10,11,23 Failure of EndoAnchor penetration will most of the time be a combination of factors causing a >2-mm gap between the endograft and aortic wall (eg, thrombus, calcium, undersized graft), and therefore a single predictor of failure of EndoAnchor penetration cannot be identified from the current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, implantation is contraindicated when one must overcome >2-mm gaps in undersized endografts or gaps due to dilation of the neck after EVAR. 1,4,10,11,23 Failure of EndoAnchor penetration will most of the time be a combination of factors causing a >2-mm gap between the endograft and aortic wall (eg, thrombus, calcium, undersized graft), and therefore a single predictor of failure of EndoAnchor penetration cannot be identified from the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Challenging proximal aortic neck anatomy leads to insufficient sealing or fixation and strongly influences the occurrence of neck-related complications, such as type IA endoleak and endograft migration. [1][2][3] The Heli-FX EndoAnchor System (Medtronic Vascular, Santa Rosa, Calif) was developed to increase migration resistance and to improve sealing of endografts in the aortic neck. Experimental studies demonstrated that EndoAnchors can significantly improve proximal fixation and sealing by securing the proximal endograft to the aortic wall.…”
mentioning
confidence: 99%
“…The endostapling systems were developed to improve sealing at the proximal neck and prevent migration. However, a systematic review of the literature was not conclusive, as no randomized controlled trials have been published [29]. Use of these systems is associated with reduced rates of type 1a endoleak and migration, suggesting reduced future need for reintervention.…”
Section: Keeping the Short Proximal Neckmentioning
confidence: 99%
“…Despite early promising results, longer-term studies are needed 15 . Endostapling and endoanchoring systems seem to be very promising and have proven to be feasible and safe 16,17 , reducing the rates of endoleak type 1A and endograft migration in a systematic review 18 . Notwithstanding, results are not conclusive, and no randomized controlled trials have been published 18 .…”
Section: E D I T O R I a Lmentioning
confidence: 99%